PERANAN SEKTOR EKONOMI DALAM PENGENTASAN KEMISKINAN DI KALIMANTAN BARAT - Murohman Murohman; Manuntun Parulian Hutagaol; Alla Asmara (IPB University, 2014)
Kalimantan Barat is a province which has the highest poverty rates among other provinces in Kalimantan. Sector’s output growth of the economy affects the redistribution of income and poverty reduction. Increased economic sector output reduce poverty through the distribution of income . Sector development policy needed to boost the economy and poverty alleviation. This study aimed to analyze the relationship between sector’s output growth of the economy and poverty reduction using InputOutput Miyazawa and decomposition of FGT (Foster-Greer-Thorbecke) poverty index. Agricultural sector has an important role in output growth, employment, and household income distribution.The decomposition method showes that direct effect of growth in manufacture alleviates poverty among poor households, and total effect of growth in agricultural sectors(food crops and estate crops) alleviates poverty among poor households in Kalimantan Barat. The main policy implication is agricultural industrialization and human capital of the poor needs to be enhanced by education and training if they are not to be sealed off the industrialization process. Key words: poverty, multiplier analysis, I-O miyazawa